Species composition and richness of avifauna in an urban area of southern Brazil - DOI: 10.4025/actascibiolsci.v32i1.6118 (Acta Scientiarum. Biological Sciences, 2009)
The urban environment has become an object of study by ornithologists, who seek to understand the relationships between this new habitat and the birds that survive within it. Aiming to investigate the composition and richness of the avifauna present at the State University of Maringá and identify temporal changes in species composition, the obtained results were compared to the study accomplished by Krügel (1998) in this same location. Thus, we performed field samplings from August 2007 to July 2008, using transects, with visual and auditive identification. We recorded 74 species belonging to 27 families from 12 orders, during 72 hours of observation. Most species were constant in the study area. The predominant trophic categories were insectivores (46%) and omnivores (20%). Comparing the analyzed periods, we verified a reduction in the number of species, besides the record of new species for the studied location.